THROUGH THE INFLUENCE OF ART: HOW CEREMONIAL CHAIRS, A TALKING STICK, AND SENATE CHAMBER DOORS BECAME PART OF ONE UNIVERSITY’S FOUNDATION FOR INDIGENIZATION (Canadian Journal of Native Studies, 2026)
N/A